Bioassay-guided isolation of cytotoxic compounds from Chrysophthalmum montanum (DC.) Boiss - Ayaz, Fatma; Kucukboyaci, Nurgun; Goren, Nezhun; Calis, Ihsan; Aydinlik, Seyma; Ulukaya, Engin; Duman, Hayri; Choudhary, Muhammad Iqbal (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Bioassay-guided isolation of the 80% methanol extract of the aerial parts of Chrysophthalmum montanum (DC.) Boiss. (Asteraceae) led to the isolation of four known guaianolide-type sesquiterpene lactones, 6 alpha-acetoxy-4 alpha-hydroxy-113H-guaia-9.11(13)-dien-12.8a-olide (1), 6 alpha-acetoxy-4 alpha-hydroxy-9 beta.10 beta-epoxy-1 beta H-guaia-11(13)-en12.8 alpha-olide (2), 4 alpha,6 alpha-dihydroxy-1 beta H,5 alpha,7 alpha H-guaia-9(10),11(13)-dien-12,8 alpha-olide (3), and (4 alpha,5 alpha,8 beta,10 beta)-4,10-dihydroxy-1,11(13)-guaidien-12,8-olide (4), along a steroidal glycoside mixture (5a and 5b). The structures of the compounds were identified on the basis of spectroscopic data. Among them, 2, 4 and a steroidal glycoside mixture were obtained from C. montanum for the first time. All isolates were also first time assayed for in vitro cytotoxicities against four human cancer cell lines, i.e. breast (MCF-7, MDA-MB 231), colon (FIT-29), and lung (PC3). Among the isolates, 1-3 showed significant inhibitory effect on the proliferation of cancer cells with viability ranging from 6.86 to 26.51%, while steroidal glycoside mixture showed no cytotoxicity, except against HT-29 (viability 61.99%). Compound 4 exhibited strong and selective cell growth inhibition against HT-29 with viability 20.99% and was identified as a promising compound with high selectivity between cancer cells and normal human lung cells (SEAS-2B), especially against HT-29 (IC50 = 12.2 pg/mL) compared to that of cisplatin. These results suggested that 4 is worthy of further study to determine its cytotoxicity mechanisms.
Keywords: Chrysophthalmum montanum; Asteraceae; Sesquiterpene lactones; Steroidal glycosides; Cytotoxicity; HT-29 colon cancer cell line; CONSTITUENTS; GUAIANOLIDES; EXTRACTS; INULEAE; PLANTS; Food Science & Technology; Toxicology